Heun Functions - 31.14 General Fuchsian Equation

From testwiki
Revision as of 12:11, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
31.14.E1 d 2 w d z 2 + ( j = 1 N γ j z - a j ) d w d z + ( j = 1 N q j z - a j ) w = 0 derivative 𝑤 𝑧 2 superscript subscript 𝑗 1 𝑁 subscript 𝛾 𝑗 𝑧 subscript 𝑎 𝑗 derivative 𝑤 𝑧 superscript subscript 𝑗 1 𝑁 subscript 𝑞 𝑗 𝑧 subscript 𝑎 𝑗 𝑤 0 {\displaystyle{\displaystyle\frac{{\mathrm{d}}^{2}w}{{\mathrm{d}z}^{2}}+\left(% \sum_{j=1}^{N}\frac{\gamma_{j}}{z-a_{j}}\right)\frac{\mathrm{d}w}{\mathrm{d}z}% +\left(\sum_{j=1}^{N}\frac{q_{j}}{z-a_{j}}\right)w=0}}
\deriv[2]{w}{z}+\left(\sum_{j=1}^{N}\frac{\gamma_{j}}{z-a_{j}}\right)\deriv{w}{z}+\left(\sum_{j=1}^{N}\frac{q_{j}}{z-a_{j}}\right)w = 0
j = 1 N q j = 0 superscript subscript 𝑗 1 𝑁 subscript 𝑞 𝑗 0 {\displaystyle{\displaystyle\sum_{j=1}^{N}q_{j}=0}}
diff(w, [z$(2)])+(sum((gamma[j])/(z - a[j]), j = 1..N))*diff(w, z)+(sum((q[j])/(z - a[j]), j = 1..N))*w = 0
D[w, {z, 2}]+(Sum[Divide[Subscript[\[Gamma], j],z - Subscript[a, j]], {j, 1, N}, GenerateConditions->None])*D[w, z]+(Sum[Divide[Subscript[q, j],z - Subscript[a, j]], {j, 1, N}, GenerateConditions->None])*w == 0
Skipped - Unable to analyze test case: Null Skipped - Unable to analyze test case: Null - -
31.14#Ex1 α + β + 1 = j = 1 N γ j 𝛼 𝛽 1 superscript subscript 𝑗 1 𝑁 subscript 𝛾 𝑗 {\displaystyle{\displaystyle\alpha+\beta+1=\sum_{j=1}^{N}\gamma_{j}}}
\alpha+\beta+1 = \sum_{j=1}^{N}\gamma_{j}

alpha + beta + 1 = sum(gamma[j], j = 1..N)
\[Alpha]+ \[Beta]+ 1 == Sum[Subscript[\[Gamma], j], {j, 1, N}, GenerateConditions->None]
Skipped - no semantic math Skipped - no semantic math - -
31.14#Ex2 α β = j = 1 N a j q j 𝛼 𝛽 superscript subscript 𝑗 1 𝑁 subscript 𝑎 𝑗 subscript 𝑞 𝑗 {\displaystyle{\displaystyle\alpha\beta=\sum_{j=1}^{N}a_{j}q_{j}}}
\alpha\beta = \sum_{j=1}^{N}a_{j}q_{j}

alpha*beta = sum(a[j]*q[j], j = 1..N)
\[Alpha]*\[Beta] == Sum[Subscript[a, j]*Subscript[q, j], {j, 1, N}, GenerateConditions->None]
Skipped - no semantic math Skipped - no semantic math - -
31.14.E3 w ( z ) = ( j = 1 N ( z - a j ) - γ j / 2 ) W ( z ) 𝑤 𝑧 superscript subscript product 𝑗 1 𝑁 superscript 𝑧 subscript 𝑎 𝑗 subscript 𝛾 𝑗 2 𝑊 𝑧 {\displaystyle{\displaystyle w(z)=\left(\prod_{j=1}^{N}(z-a_{j})^{-\gamma_{j}/% 2}\right)W(z)}}
w(z) = \left(\prod_{j=1}^{N}(z-a_{j})^{-\gamma_{j}/2}\right)W(z)

w(z) = (product((z - a[j])^(- gamma[j]/2), j = 1..N))*W(z)
w[z] == (Product[(z - Subscript[a, j])^(- Subscript[\[Gamma], j]/2), {j, 1, N}, GenerateConditions->None])*W[z]
Skipped - no semantic math Skipped - no semantic math - -